Rheological behavior of nanocellulose gels at various calcium chloride concentrations. (15th November 2021) - Qu, Rui-jing; Wang, Yong; Li, Dong; Wang, Li-jun
Abstract: In this work, the effects of calcium chloride (CaCl2 ) concentration on the creep-recovery, linear and nonlinear rheological behavior of nanocellulose gels had been investigated to quantify gel properties. The absolute zeta potential of nanocellulose gels were decreased as the CaCl2 concentration increased, which was related to the electrostatic repulsion that origin from carboxyl group could be effectively screened with increasing CaCl2 concentration. Rheological measurements further confirmed this result for nanocellulose gels, which revealed that the increased modulus and viscoelastic properties were obtained in the presence of CaCl2 . The rheological properties of nanocellulose gels were showed to depend on CaCl2 concentration. The enhanced gel network structure was related to the Ca 2+ ions that promoted crosslink between nanocellulose by salt bridge. This work highlighted the potential of using electrostatic complexation between nanocellulose and Ca 2+ ions to form gels, and demonstrated the tunability of the rheological behavior by adjusting the concentration of CaCl2 . Graphical abstract: Unlabelled Image Highlights: The creep-recovery, linear, and nonlinear rheological behavior of nanocellulose gels were studied. An enhanced gel network structure was formed with increase of CaCl2 concentration. Nanocellulose gels showed less deformable network structure in the presence of CaCl2 . Nanocellulose gels exhibited different nonlinear behavior at large strain amplitude.